2016
DOI: 10.21276/aimdr.2016.2.5.mb3
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Microbiological Profile of Respiratory Tract Infection (RTI) in Patients Attending Gauhati Medical College & Hospital

Abstract: Background: Respiratory tract infections (RTI's) are the most frequent infections among patients. The consequences of increased drug resistance are far reaching since bacterial infection of the respiratory tract (RT) is a major cause of death from infectious disease. Objective: This study was focused on obtaining a comprehensive insight into the microbial profile, its prevalence and the antibiotic susceptibility patterns of the isolates in respiratory tract infections. Methods: The present study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…32,33 In contrast, other reports mentioned the Gram-negative species Pseudomonas aeruginosa and Klebsiella pneumoniae as the predominant strains. [34][35][36] Overall resistance pattern among isolates for commonly used antibiotics was high, but varied against one antibiotic to others (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In contrast, other reports mentioned the Gram-negative species Pseudomonas aeruginosa and Klebsiella pneumoniae as the predominant strains. [34][35][36] Overall resistance pattern among isolates for commonly used antibiotics was high, but varied against one antibiotic to others (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, Nidhi et al, and Sarmah et al found amoxyclav to be more sensitive against gram negative bacteria. 16,17 Our study reported that the gram-positive bacteria showed 100% sensitivity for vancomycin and teicoplanin. Penicillin, cotrimoxazole and ciprofloxacin showed highest resistance.…”
Section: Discussionmentioning
confidence: 69%
“…In studies by Kottman et al 20 and Bari et al 23 , predominance of aerobic Gram-negative bacteria over Gram positive bacteria was observed. Klebsiella was also the most common pathogen isolated from studies done by Sarmah et al 24 , Lin et al 25 and Singh et al 26 . Pseudomonas aeruginosa was the commonest isolate in a study done by Magazine et al 27 in 2013.…”
Section: Discussionmentioning
confidence: 97%